Comparison of Intercostal Nerve Block Versus Patient-Controlled Intravenous Analgesia for Post Thoracotomy Pain - Reema Meena; Renu Garg; Arun Garg; Shunmugam (Indonesian Journal of Anesthesiology and Reanimation, 2025)
Introduction: Acute pain after thoracic surgery is frequent, intense and can raise morbidity. Effective postoperative pain control is essential to support early mobilization, optimal respiratory function, and recovery. Different pain relief methods, such as systemic opioids, patient-controlled analgesia, and intercostal nerve blocks, have been studied to reduce problems and enhance recovery for patients who have had thoracic surgery. Objectives: This research aims to compare the difference in analgesic effect of intercostal nerve block (ICNB) versus patient-controlled intravenous analgesia (PCIA) for post-thoracotomy analgesia in cardiac surgery. Methods: This prospective, single-blind, randomized comparative study involved 128 patients aged 30-60 years undergoing cardiac surgery through a thoracotomy under general anesthesia. Patients were randomly assigned to two groups. Group A received ICNB with 2.5 mg/kg of 0.5% ropivacaine and 0.5 mcg/kg fentanyl at the end of surgery; rescue analgesia with fentanyl 1mcg/kg was given if VAS score exceeded 4 within 24 hours post-intubation. Group B received PCIA with IV fentanyl (25 mcg/ml) at a basal rate of 1 ml/hour, with 1 ml bolus doses available every 15 minutes post-extubation for 24 hours. Pain was assessed using the Visual Analogue Scale (VAS), and total fentanyl consumption and sedation score were recorded. Significance level was kept at 95%. Results: The demographic data were comparable between the two groups. The VAS score was significantly lower in the ICNB group than in the PCIA group (p value < 0.05). The total dose of fentanyl required in 24 hours after extubation was significantly higher in the PCIA group than in the ICNB group. The mean Ramsay sedation score was higher in the PCIA group compared to the ICNB group. Patients in ICNB group showed a lower incidence of side effects. Conclusion: Our study suggests that the ICNB is more effective than PCIA for post-thoracotomy analgesia and also requires a lesser total dose of opioid.